2019
DOI: 10.1186/s12913-019-4711-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling patients’ time, travel, and monitoring costs in anticoagulation management: societal savings achievable with the shift from warfarin to direct oral anticoagulants

Abstract: BackgroundAnticoagulation therapy is used for atrial fibrillation (AF) patients for reducing the risk of cardioembolic complications such as stroke. The previously recommended anticoagulant, warfarin, has a narrow therapeutic window, and it requires regular laboratory monitoring, unlike direct oral anticoagulants (DOAC). From a societal perspective, it is important to measure time and travel costs associated with warfarin monitoring to better compare the total therapy costs of these two alternative forms of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
(35 reference statements)
0
15
0
1
Order By: Relevance
“…However, the total costs associated with warfarin treatment may have been underestimated due to the exclusion of time and travelling costs which have been estimated to form 26.6% of total therapy costs for warfarin in Finland. 47 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the total costs associated with warfarin treatment may have been underestimated due to the exclusion of time and travelling costs which have been estimated to form 26.6% of total therapy costs for warfarin in Finland. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that there may be inequalities in access to DOACs as DOAC-treated patients tend to have higher education and income levels. 45,46 In our NAXOS-study based analysis, the relative treatment effects were obtained from analyses where apixaban was separately compared to each of the comparators using propensity score matching. 7 Because of this, the current analysis should not be interpreted to provide evidence of the relative cost-effectiveness between the other three anticoagulants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that multiple factors influence the choice of travel mode, such as age, gender, income, distance, physical functioning, weather, car ownership and place of residence [ 38 , 39 ]. Due to a lack of travel mode information by EHRs on non-reimbursed journeys, we applied prior study classifications to set the travel modes for journeys [ 31 , 40 ]. The selection criteria are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Indirect costs have often been ignored or generalised based on economic evaluations, although the cost of INR monitoring represents a large proportion of the annual cost of warfarin therapy. A recent study has estimated that almost 25% of warfarin therapy costs consist of indirect costs when patients need frequent monitoring at laboratory units [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The selected data were originally used for other research purposes and includes mainly patients with alcohol-use disorder (Rautiainen, Ryynänen, and Laatikainen 2018), type 2 diabetes (Toivakka et al 2018), coronary heart disease (Repo et al 2018) and anticoagulation (Leminen et al 2019). The data is therefore not an exact representation of the entire population, but its geographic distribution is rather similar, and it is useful for our study.…”
Section: Facility Location Optimisationmentioning
confidence: 99%